A simple method for optimizing wave energy harvest from a spar buoy WEC (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Spar buoys are widely employed in ocean engineering. While the use of spar buoys as part of a WEC have been ample, most have extracted energy in heave, and few have been successful. A novel approach to the use of a spar buoy as the inertial body of a two body floating WEC that extracts torsional energy. Levers connected to a cylindrical shaped float are amplified by gearboxes to drive the PTO on the spar buoy.The WEC adopts the design of a well known vessel, R/P Floating Instrumented Platform (FLIP), which is towed like a marine vessel and flipped into a spar buoy configuration for conducting research. This simple design allows the WEC to take advantage of existing marine vessel infrastructure to lower operating costs.The WEC is a highly adaptable, passive controlled WEC that can optimize energy harvest for a broad spectrum of wave conditions. Results from WEC-Sim simulation are presented in this study, which show the WEC’s simple methods to maximize energy extraction.